A Prospective Observational Study to Assess Attachment Representations With Regard to Neurocognitive and Behavioral Outcomes in Children Born Very Prematurely in the Loire Infant Follow-Up Team (LIFT Cohort) - Riquin, Elise; Sandnes, Ramona; Bacro, Fabien; Vinay, Aubeline; Miljkovitch, Raphaële; Rouger, Valérie; Rakotonjanahary, Josué; Gascoin, Géraldine; Müller, Jean-Baptiste (Frontiers in Pediatrics, 2022)
Context and purpose Prematurity is a situation that can disrupt parent-child interactions. We hypothesize that establishing relationships with parents in a context of extreme prematurity can alter the development of secure attachment representations in the child. Furthermore, we hypothesize that secure maternal representations and their possible interactions with prematurity factors prevent the development of insecure or disorganized attachment in the child. In addition, maternal representations and their possible interactions with factors related to prematurity may prevent or accentuate the development of an insecure or disorganized attachment in the child. Methods and analysis This is a longitudinal, prospective, exploratory, and bi-centric study. Children born in the neonatal intensive care units of Angers or Nantes University Hospitals with a gestational age of up to 28 weeks will be included in the study. The main objective is to describe the attachment representations at 3 and 5 years through the Attachment Story Completion Task scales and to analyze them in regard to the children’s neurocognitive and behavioral outcomes as well as maternal attachment and mental health. Ethics The study file received a favorable opinion for the implementation of this research on February 18, 2020 - ID-RCB no. 2019-A03352-55 (File 2-20-007 id6699) 2°HPS. This study has received authorization from the French Data Protection Authority (CNIL) under no. 920229. Discussion A better understanding of attachment representations in extreme prematurity and their possible associations with children’s neurocognitive and behavioral outcomes as well as maternal attachment and mental health could pave the way for individualized care at an early stage, or even interventions during the neonatal period to improve the outcome of these vulnerable newborns. Trial registration [ClinicalTrials.gov], identifier [NCT04304846].